TRANSFORMATION OF COMPETENCY MAPPING THROUGH A MODEL OF SIMPLIFYING THE ORGANIZATIONAL STRUCTURE OF THE REGIONAL APPARATUS AT THE PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY OGAN ILIR REGENCY - Wilson Efendi; Alfitri; Raniasa Putra; Alamsyah (SOSIOEDUKASI, 2026)
This study aims to analyze the transformation of the competency mapping of the State Civil Apparatus (ASN) through a model of simplifying the organizational structure of the regional apparatus at the Ogan Ilir Regency Personnel and Human Resources Development Agency (BKPSDM), identifying the supporting and inhibiting factors, and formulating an optimal competency transformation model. The research uses a descriptive qualitative approach with an interpretive-constructivist paradigm. Data was obtained through in-depth interviews, observations, and documentation studies, then analyzed using the Miles, Huberman, and Saldaña interactive model which included data condensation, data presentation, and conclusion drawn. The results of the study show that the simplification of the organizational structure has changed the orientation of ASN management from an administrative approach to a competency-based approach through strengthening functional positions and utilizing the results of competency mapping in placement, career development, and ASN competency development. This transformation is supported by leadership commitment, bureaucratic reform regulations, and the use of information technology, but still faces obstacles in the form of budget limitations, integration of competency data that is not optimal, and limited management resources. This research produces a competency mapping transformation model that integrates position analysis, technical, managerial, and socio-cultural competency mapping, digitization of competency data, competency development based on organizational needs, as well as the application  of talent management and succession planning to support a professional, adaptive, and merit-based bureaucracy.